A Research Note on the Public–Private Partnership of India's Infrastructure Development. (December 2014) - Nagesha G.,; Gayithri, K.
To clip infrastructure inadequacy both in India and rest of the World Public–Private Partnerships (PPPs) emerged as an alternative to the traditional mode of infrastructure provisions of governments. The article analyses trends and patterns of various infrastructure sectors and regional distribution of PPPs at India's national and sub-national levels to identify to what extent this has been able to curb infrastructure deficit. The growth empirics reveal that there has been a sharp increase in the number of PPP projects. This has been contributing to enhanced regional and sectoral infrastructure availability. In addition, the article has observed that PPP projects under the national highway category are time and cost efficient as compared to the non-PPP projects. However, these projects have tended to concentrate in certain sector and regions, thus being the case both in the global and Indian context. This is despite the incentives available for the purpose. The present article explores the possible reasons for this uneven growth in India to be due to differences in the political will among the national and sub-national governments in promotion of the infrastructure PPP policies, effective functioning of governments' various infrastructure executive departments including PPP nodal agencies for identifying, executing, coordinating various departments and in promotion of projects for hassle-free quick implementation and to redress the various differences. Financial assurances to the concessionaires on their investments, availability of land and other incentives like tax incentives, capital grant (viability gap funding), and coordination by users and nature of project risks, and the degree of private sector risk management capacity are some the important factors explaining the differences.